A new species of Synanthedon Hübner (Lepidoptera: Sesiidae) from the coastal South Carolina and central Alabama, United States - Jr, William H Taft; Lopresti, Eric F.; Cognato, Anthony I. (Zootaxa, 2025)
A clearwing moth species, Synanthedon nielseni sp. nov. is described from South Carolina and Alabama. The recognition of this new species is based on a phylogeny estimated from mitochondrial cytochrome oxidase I of 26 North American Synanthedon species including individuals from various locations. Synanthedon nielseni sp. nov. was monophyletic and differed from Synanthedon refulgens and Synanthedon arkansasensis by a mean of 11.0 % COI pairwise “p” distance, coloration, and genitalic morphology.